2019
DOI: 10.1186/s13024-019-0337-1
|View full text |Cite
|
Sign up to set email alerts
|

Lack of hepatic apoE does not influence early Aβ deposition: observations from a new APOE knock-in model

Abstract: Background The apolipoprotein E (APOE) gene is the strongest genetic risk factor for late-onset Alzheimer disease (AD). ApoE is produced by both astrocytes and microglia in the brain, whereas hepatocytes produce the majority of apoE found in the periphery. Studies using APOE knock-in and transgenic mice have demonstrated a strong isoform-dependent effect of apoE on the accumulation of amyloid-β (Aβ) deposition in the brain in the form of both Aβ-containing amyloid plaques and cerebral amyloid a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
95
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(99 citation statements)
references
References 98 publications
(166 reference statements)
4
95
0
Order By: Relevance
“…Importantly, we also observed that AZ7235 has little to no effect on apoE and ABCA1 in murine glial cells, even when these cells express human apoE protein. The human APOE targeted-replacement mice we used to cultivate primary glial cells were generated using a knock-in strategy that retains human introns between exons 2-3 and 3-4 but retains the murine 5'UTR and 3'UTR sequences [37]. Murine apoE is known to be much less responsive to known apoE regulators such as GW3965 [32] and Bexarotene [63], thus we expected a reduced signal in primary murine glia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, we also observed that AZ7235 has little to no effect on apoE and ABCA1 in murine glial cells, even when these cells express human apoE protein. The human APOE targeted-replacement mice we used to cultivate primary glial cells were generated using a knock-in strategy that retains human introns between exons 2-3 and 3-4 but retains the murine 5'UTR and 3'UTR sequences [37]. Murine apoE is known to be much less responsive to known apoE regulators such as GW3965 [32] and Bexarotene [63], thus we expected a reduced signal in primary murine glia.…”
Section: Discussionmentioning
confidence: 99%
“…Primary human astrocytes (cat# 1800) and brain vascular pericytes (cat# 1200) were acquired from ScienCell. Human APOE3 targeted-replacement mice [37] were obtained from the Cure Alzheimer Fund and primary murine mixed glia were cultured from postnatal day 0-2 pups as described [38]. The LXR agonist T0901317 was acquired from Sigma-Aldrich (cat# 575310).…”
Section: Cell Models and Reagentsmentioning
confidence: 99%
“…The majority of these findings have been obtained by studying human APOE isoform-specific targeted replacement (TR) mice crossed with transgenic AD mouse models. Recently, to address the role of peripheral and central APOE, respectively, in AD, novel lines of human APOE-knock in (KI) mice have been generated [79]. It was shown that deletion of hepatic APOE, which led to a marked decrease in peripheral APOE levels, did not affect cerebral Aβ deposition in the APP/PS1 transgenic mouse model of AD.…”
Section: Amyloid Pathologymentioning
confidence: 99%
“…More recently, it has been shown that microglia drive tau pathology and neurodegeneration depending on APOE [123]. It also appears that the inflammatory response in the brain is regulated specifically by microglia-derived APOE [79]. In addition, TREM2 has been shown to regulate cholesterol metabolism in microglia, particularly upon chronic phagocytic challenge, and TREM2-deficient microglia fail to upregulate lipid metabolism genes including APOE, leading to intracellular accumulation of cholesteryl esters, which is rescued by treatment with pharmacological agents to inhibit CE synthesis or increase expression of cholesterol efflux genes [124].…”
Section: Neuroinflammationmentioning
confidence: 99%
“…These mice have impaired synaptic plasticity but their spatial memory skills are intact [24], suggesting that peripheral and CNS APOE may have distinct effects on CNS function. On the other hand, absence of hepatic APOE does not affect the APOE4dependent induction of Aβ pathologies in young APP/ PS1 female mice, suggesting that plasma APOE4 may have little influence on initiation of Aβ pathologies in the brain [27]. With this knowledge, it is reasonable to explore treatment options that would preferentially modify the CNS pool of APOE without affecting the peripheral sources, thus also avoiding systemic metabolic syndromes.…”
Section: Introductionmentioning
confidence: 99%